La transformation de l'école secondaire en Suède : marchandisation, dissolution et reconstruction des frontières institutionnelles et sociales - Mikael Palme; Elisabeth Hultqvist (Nantes Université, 2009)
The article analyzes the effects of the current transformations of Swedish upper secondary education emerging from the marketization brought about by the introduction of school vouchers in the 90s and, in the Stockholm region, of a free competition for admission. The rapid expansion of private or "independent" schools and the double competition between schools trying to attract students and students competing to enter into schools have resulted in the creation of numerous "profiled" study programs offering a unique mix of courses. Interviews show that the free choice of education in combination with blurred institutional frontiers make families' educational strategies increasingly dependant on their culturally framed capacity to interpret and "construct" educational differences. A statistical analysis of student recruitment in the Stockholm region shows that the space of upper secondary education comprises two dimensions. A first one that opposes socially and scholarly highly ranked schools and study programs to those with a low recruitment profile, and a second one separates schools recruiting students from families with a strong cultural capital to those receiving most of their students from families with strong economic capital. In this increasingly hierarchic and structured universe, individual schools tend to occupy positions pertaining to specific niches. An analysis of the Internet home pages of 39 upper secondary schools show that these oppositions are mirrored by the ones that structure the universe of symbolic values put forward at these pages.